Analyzing new ventures’ innovation generation and adoption: a configurational analysis from the optimal distinctiveness perspective - Xie, Zhimin; Xie, Lingmin; Liu, Li (Journal of Business Economics and Management, 2024)
The institutional theory literature focuses on the legitimization of new ventures’ innovative behaviors, while the entrepreneurial orientation literature emphasizes differentiation of the pursuit of innovation by new ventures. We apply the optimal distinctiveness perspective to examine how the institutional environment and entrepreneurial orientation jointly influence two modes of innovation – innovation generation and innovation adoption – in new ventures. We employ fuzzy-set qualitative comparative analysis (fsQCA) based on country-level data obtained from the Global Entrepreneurship Monitor (GEM) project. Our findings reveal that there are five equifinal optima of distinctiveness rather than a one-size-fits-all optimal distinctiveness for high innovation generation and high innovation adoption, respectively. Moreover, the orchestrating mechanisms of the two modes of innovation are different: that of innovation generation is threshold orchestration and that of innovation adoption is compensatory orchestration. Furthermore, except for the difference, we also identify something similar shared by mechanisms of innovation generation and innovation adoption. These results extend the optimal distinctiveness theory by empirically verifying equifinality in optimal distinctiveness and articulating different practices of threshold orchestration and compensatory orchestration, and also contribute to the innovation literature by examining the differences and similarities of the mechanisms of innovation generation and innovation adoption.